Occult Breast Carcinoma Presenting as Gastrointestinal Metastases. (22nd December 2009) - Neal, Lonzetta; Sookhan, Nicole; Reynolds, Carol
Abstract : Occult breast cancer has frequently been described as presenting as axillary lymph node metastases but rarely as gastrointestinal metastases, Varadarajan et al. (2007). In extremely rare situations, cancerous lesions identified in the gastrointestinal tract have been determined to be metastatic lesions from primary breast cancers, Taal et al. (2000). We report a case of an occult lobular adenocarcinoma presenting as gastrointestinal metastases. It is essential that the possibility of lesions found in the gastrointestinal tract originating from distant or occult cancers be considered in order that appropriate therapeutic options may be discussed and considered early after diagnosis.